Thematic Learning Plans with the RADEC Learning Model in Building Students' Environmental Care Character in Elementary Schools - Utsman, Arif; Markhamah, Markhamah; Rahmawati, Laili Etika; Minsih; Widyasari, Choiriyah (Universitas Pendidikan Ganesha, 2022)
The importance of elementary school teachers' understanding of thematic learning planning dramatically influences forming students' character to care for the environment. Regarding the importance of thematic learning planning, a suitable learning model for shaping students' character to care for the environment is the RADEC learning model. This study aims to analyze the planning and implementation of thematic learning with the RADEC model to increase the character of caring for the environment. The research design used is the explorative description. Data collection techniques using observation, interviews, and documentation. Data analysis techniques are data reduction, display, and verification. The study results show that teachers understand how to develop thematic learning plans using the RADEC learning model in elementary schools. Implementation of thematic learning with the RADEC learning model, namely preliminary activities, includes learning activities carried out by the teacher, including preparing students both psychologically and physically, reading prayers, and asking how students are doing. Then in the core activities, the teacher tries to facilitate students in reading, answering, discussing, explaining, and creating according to the syntax contained in the RADEC learning model.